2004
DOI: 10.1111/j.1742-7843.2004.pto940502.x
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Hypersecretion after Inhibition of Gastric Acid Secretion

Abstract: Drugs inhibiting gastric acid secretion are widely used because of the high prevalence of acid-related disorders. However, from clinical experience it seems that symptom relapse is common after withdrawal of these drugs. Experimental as well as clinical studies have demonstrated an increased acid secretion after a period of treatment with either histamine 2 receptor antagonists or proton pump inhibitors. Rebound hypersecretion is likely to reflect the following sequence of events: Long-term inhibition of acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…Increased gastric acid secretion is well described after stopping the long-term use of histamine H 2 -receptor antagonists[18,65], however its occurrence after the prolonged use of PPIs is controversial[18,66•]. Some studies provide evidence it occurs in 60–90% of patients after long-term PPI usage[18,65].…”
Section: Advances In Other Nonzes Gastric Acid Hypersecretory Smentioning
confidence: 99%
See 1 more Smart Citation
“…Increased gastric acid secretion is well described after stopping the long-term use of histamine H 2 -receptor antagonists[18,65], however its occurrence after the prolonged use of PPIs is controversial[18,66•]. Some studies provide evidence it occurs in 60–90% of patients after long-term PPI usage[18,65].…”
Section: Advances In Other Nonzes Gastric Acid Hypersecretory Smentioning
confidence: 99%
“…Some studies provide evidence it occurs in 60–90% of patients after long-term PPI usage[18,65]. Evidence has been provided that the mechanism of the rebound hypersecretion post use of PPIs was, at least in part, mediated by the hypergastrinemia that occurred as result of the marked inhibition of the acid secretion by the PPI[18,65].…”
Section: Advances In Other Nonzes Gastric Acid Hypersecretory Smentioning
confidence: 99%
“…We believe this decrease in periampullary cancer risk as cDDD levels increase beyond 180 days is partly attributed to mechanism of PPI tolerance. Studies on H2RAs (another medication commonly used for GERD and PUD) have found that tolerance of the drug decreases after previous drug treatments, especially intravenous medication 39, 40. It is possible that patients on long‐term PPI use encounter similar tolerance problems with PPI just as patients experience with H2RAs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased gastric acid secretion is well described after stopping the long-term use of H 2 RA [52,53], but its occurrence after the prolonged use of PPIs is controversial. It seems that there is no strong evidence for a clinically relevant increased acid output after PPI therapy is stopped [51,52,53]. Three uncontrolled trials nevertheless suggested an increase in acid secretory capacity in H. pylori- negative subjects after 8 weeks of treatment [54,55].…”
Section: What Do We Know About Unmet Needs?mentioning
confidence: 99%
“…Rebound is clinically important because it seems that it contributes to the recurrence of GERD [50]. There are four mechanisms to explain rebound: upregulation of H 2 receptors, hypergastrinemia-stimulating histamine release by enterochromaffin-like cells, increase of parietal cell mass and upregulation of H + ,K + -ATPase activity [51]. Increased gastric acid secretion is well described after stopping the long-term use of H 2 RA [52,53], but its occurrence after the prolonged use of PPIs is controversial.…”
Section: What Do We Know About Unmet Needs?mentioning
confidence: 99%